Effectiveness of Installment Payment Management Using Recurring Scheduling to Cashier Performance - Aini, Qurotul; Alwiyah, Alwiyah; Putri, Dian Mustika (APTISI Transactions on Management (ATM), 2019)
The purpose of writing this paper is to provide an overview of the progress of cloud-based accounting systems that are applied to Student Financial Services (cashiers) at Raharja College. Implementation of this system is due to the existence of good management in college to solve the problem. This recurring scheduling feature in the cloud-based accounting system is a new breakthrough that is useful for paying for lectures that use the installment payment system. Where, students can pay tuition twice in installments, namely the period before the midterm exam and before the final exam. This feature is useful to minimize the existence of human error because it forgets billing input, bills are inputted twice with the same nominal, and sending invoices via email is not monitored. So, with the implementation of this system, the cashier's work on students in the installment system can be more effective and have a positive impact on the cashier's performance. This research was conducted using the literature review research method, to find useful theoretical foundations as a reference for solving problems that occur.